Analisis Kebutuhan Pengembangan Instrumen Penilaian Berbasis Kebudayaan untuk Mengukur Kemampuan Berpikir Kritis & Kebhinekaan Global - Anisa Ayu Solikah; Sulistyo Saputro; Sri Yamtinah (Universitas Sebelas Maret, 2025)
The development of the 21st century has resulted in technology continuing to develop which has given rise to global interactions and connections. To overcome the loss of national culture, critical thinking ability and understanding of global diversity need to be implemented in schools. This can be done through introducing the culture around students. However, in reality, until now learning and assessment have not focused enough on critical thinking skills and global diversity because they focus more on content mastery and most teachers emphasize material mastery when conducting assessments. Therefore, to prove this problem, a needs analysis is needed. The method used in this research is through a qualitative descriptive method with documentation, literature study, and interviews with five science teachers in several junior high schools in the city of Surakarta. While quantitative through a questionnaire filled in by 42 students. The result of this needs analysis is that the development of assessment instruments used to measure critical thinking ability and culture-based global diversity at the junior high school level is very necessary, especially in science learning. It is hoped that the implications of the results of this research will be future research development regarding culture-based assessment instruments to measure critical thinking skills and global diversity at the junior high school level.